Intragenic KANSL1 mutations and chromosome 17q21.31 deletions: broadening the clinical spectrum and genotype–phenotype correlations in a large cohort of patients. Issue 12 (30th September 2015) - Zollino, Marcella; Marangi, Giuseppe; Ponzi, Emanuela; Orteschi, Daniela; Ricciardi, Stefania; Lattante, Serena; Murdolo, Marina; Battaglia, Domenica; Contaldo, Ilaria; Mercuri, Eugenio; Stefanini, Maria Chiara; Caumes, Roseline; et al.
Abstract : Background: The 17q21.31 deletion syndrome phenotype can be caused by either chromosome deletions or point mutations in the KANSL1 gene. To date, about 60 subjects with chromosome deletion and 4 subjects with point mutation in KANSL1 have been reported. Prevalence of chromosome deletions compared with point mutations, genotype–phenotype correlations and phenotypic variability have yet to be fully clarified. Methods: We report genotype–phenotype correlations in 27 novel subjects with 17q21.31 deletion and in 5 subjects with KANSL1 point mutation, 3 of whom were not previously reported. Results: The prevalence of chromosome deletion and KANSL1 mutation was 83% and 17%, respectively. All patients had similar clinical features, with the exception of macrocephaly, which was detected in 24% of patients with the deletion and 60% of those with the point mutation, and congenital heart disease, which was limited to 35% of patients with the deletion. A remarkable phenotypic variability was observed in both categories, mainly with respect to the severity of ID. Cognitive function was within normal parameters in one patient in each group. Craniosynostosis, subependymal heterotopia and optic nerve hypoplasia represent new component manifestations. Conclusions: In KANSL1 haploinsufficiency syndrome, chromosome deletions are greatly prevalent compared with KANSL1 mutations. The latter are sufficient in causing the full clinical phenotype. The degree of intellectual disability (ID) appears to be milder than expected in a considerable number of subjects with either chromosome deletion or KANSL1 mutation. Striking clinical criteria for enrolling patients into KANSL1 analysis include speech delay, distinctive facial dysmorphism, macrocephaly and friendly behaviour.